Implementation of a nurse-delivered, community-based liver screening and assessment program for people with metabolic dysfunction-associated steatotic liver disease (LOCATE-NAFLD trial) - Michelle J. Allen; Ruth Tulleners; David Brain; James O’Beirne; Elizabeth E. Powell; Adrian Barnett; Patricia C. Valery; Sanjeewa Kularatna; Ingrid J. Hickman (BMC Health Services Research)
Abstract Background With the high burden of Metabolic dysfunction-associated steatotic liver disease (MASLD), (previously known as Non-Alcoholic Fatty Liver Disease - NAFLD) in the community, current models of care that require specialist review for disease risk stratification overwhelm hospital clinic capacity and create inefficiencies in care. The LOCal Assessment and Triage Evaluation of Non-Alcoholic Fatty Liver Disease (LOCATE-NAFLD) randomised trial compared usual care to a community-based nurse delivered liver risk assessment. This study evaluates the implementation strategy of the LOCATE model. Methods The evaluation used mixed methods (quantitative trial data and qualitative framework analysis of semi-structured interviews) to explore the general practitioner (GP) and patient perspectives of acceptability (Acceptability Framework), and factors associated with reach, effectiveness, adoption, implementation, and maintenance (RE-AIM framework) of the LOCATE model of care. Results The LOCATE model was considered highly acceptable by both patients and GPs. The model of care achieved appropriate reach across the participating health services, reaching high-risk patients faster than usual care and with predominantly positive patient experiences. A notable reduction in anxiety and stress was experienced in the intervention group due to the shorter waiting times between referral and assessment. There was an overall perception of confidence in nursing staff capability to perform the community-based screening and GPs indicated confidence in managing low-risk MASLD without the need for specialist review. Challenges to implementation, adoption and maintenance included variable prioritisation of liver disease assessment in complex cases, the need for further GP training in MASLD assessment and treatment pathways, available funding and referral pathways for community screening, and accessibility of effective diet and exercise professional support. Conclusion Nurse delivered community-based liver screening is highly acceptable to GPs and patients and has shown to be an effective mechanism to identify high risk patients. Adoption and maintenance of the model of care faces significant challenges related to affordable access to screening, prioritisation of liver disease in complex patient cohorts, and unresolved difficulties in prescribing effective strategies for sustained lifestyle intervention in the primary care setting. Trial registration The trial was registered on 30 January 2020 and can be found via Australian New Zealand Clinical Trials Registry (ANZCTR) – ACTRN12620000158965.